Peran Resiliensi Dalam Pengembangan Diri Remaja: Studi Literatur - Ramadhani, Anita; Nur, Haerani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Adolescence is a transitional period characterized by various physical, psychological and social challenges, so the ability to adapt and survive is very important. Resilience is understood as an individual’s ability to rise from adversity, manage stress, and grow into a stronger person. This study aims to explore conceptual and empirical understanding of the role of resilience in supporting adolescent self-development. This research uses a literature study method or literature review. This research uses the literature study method. The results of this study indicate that resilience plays a significant role in shaping aspects of adolescent self-development, both academically, emotionally, socially and spiritually. The factors that form resilience include internal and external aspects and the provision of effective interventions. Thus, strengthening resilience is an important strategy in creating adolescents who are resilient, independent, and ready to face the challenges of life. This study is expected to be the basis for the development of educational policies and programs that focus on building adolescent character through strengthening resilience.